A genetic algorithm approach for aircraft landing problem - (:unkn) unknown (Computers and Industrial Engineering, 2014)
Air traffic is growing at the recent years but there is a little change at the number of airports and runways. For this reason, Air Navigation Service Providers are forced to improve the efficiency of the airports. Building new airports is not a solution; one of the ways to improve efficiency is optimizing aircraft scheduling. Optimum aircraft scheduling brings too many benefits that are minimizing the number of late aircrafts, maximizing airport capacity, decreasing the workforce of air traffic controller, decreasing air pollution and fuel consumption.
Keywords: Aircraft; Aviation; Genetic algorithm; Scheduling